Analisis Peranan Sektor Pertanian di Provinsi Nusa Tenggara Timur - Fadhlan Zuhdi (Fakultas Pertanian, Universitas Timor, 2021)
East Nusa Tenggara Province (NTT) is a province that has a lot of potential natural resource due to its diverse demographics from volcanoes to savanna and steppe. This potential makes NTT Province feasible to be developed, especially in the agricultural sector. Potential analysis of the agricultural sector was carried out to measure the role of the agricultural sector for economic growth in NTT Province using the Klassen Typology Method, Location Quotient (LQ) and Shift Share analysis. The results with Klassen Typology Method show that the agricultural sector is in quadrant II, which is an advanced but depressed sector. This reflects that the agricultural sector is the dominant sector for economic growth in NTT Province during the analysis period. However, over time, other sectors had faster growth rates than the agricultural sector. In addition, the results of the LQ analysis state that the agricultural sector is the basis of the sector in NTT Province, while the Shift Share analysis states that the growth of the agricultural sector in NTT Province has a faster growth than the national agricultural sector.